Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Pendidik dan Tenaga Kependidikan di Pondok Pesantren Modern Kecamatan Cipondoh Kota Tangerang - Ahmad Fahrudin; Husain Nurisman (Jurnal Ilmiah Wahana Pendidikan, 2020)
The purpose of this study was to determine the effect of compensation on the performance of educators and education personnel, the effect of the work environment on the performance of educators and education personnel and the effect of compensation and work environment on the performance of educators and education personnel. The place of research was carried out at the Modern Islamic Boarding School, Cipondoh District, Tangerang City. This research is a descriptive research with a quantitative approach. The research method uses survey methods, data collection techniques used in this study are observation, documentation and questionnaires (questionnaires), the measurement scale used is the Likert scale. After the researchers analyzed the data, the results of the t-test partially showed that compensation (X1) had no effect on the performance of educators and education personnel, where tcount -0.166 < ttable 2.002. The results of the t test partially show that the work environment (X2) has an effect on the performance of educators and education personnel where t count is 4,665 > t table 2,002. The results of the F test show that compensation and work environment simultaneously affect the performance of educators and education personnel, where Fcount 4,665 > Ftable 3,16.Compensation, Work Environment and Performance of Educators and Education Personnel. research method used a qualitative approach by random sampling. The results of this study are that the majority of innovation decisions in some of boarding school at Cipondoh distric are included in the type of collective innovation decisions, although some are categorized as authority innovation decisions. This study succeeded in showing that compensation has no effect on the performance of Modern Islamic Boarding School Educators and Education Personnel.